Annali, Ruedi, Mami.: Das Diminutiv und seine Rolle bei der Entstehung und Verfestigung onymischer Neutra - Christen, Helen; Baumgartner, Gerda (Linguistik Online, 2021)
Data of the dialect research project “Das Anna und ihr Hund. Weibliche Rufnamen im Neutrum” indicate the important role of diminutive names in terms of the historical develop-ment and consolidation of the onymic neuter gender assignment. The focus in the present arti-cle lies therefore on the forms and the use of diminutive names (e. g. Anneli, Ruedi) in Swiss-German dialects.Based on diachronic evidence from literary works and regional dictionaries, differences in the diminution of male and female names are historically traced and substantiated. It is for prag-matic reasons that female kinship names (e. g. Mami) are crystallized to be the last bastion for the neutral gender assignment which opens up new perspectives on the diachronic emergence of this phenomenon. The consideration of further onymic suffixes in the outlook brings up a debate on the disagreement of gender and sex which is considered to be a possible objective of the suf-fixation itself.